What you can do to avoid AIDS - Johnson, Earvin, 1959- (New York : Times Books, 1992)
Explains what HIV and AIDS are and how readers can protect themselves and others from being infected.
Includes index.
8 13 16 18 20 32
Keywords: AIDS (Disease) -- Juvenile literature; AIDS (Disease).